2000
DOI: 10.1038/78531
|View full text |Cite
|
Sign up to set email alerts
|

Heritable gene silencing in Drosophila using double-stranded RNA

Abstract: RNA-mediated interference (RNAi) is a recently discovered method to determine gene function in a number of organisms, including plants, nematodes, Drosophila, zebrafish, and mice. Injection of double-stranded RNA (dsRNA) corresponding to a single gene into organisms silences expression of the specific gene. Rapid degradation of mRNA in affected cells blocks gene expression. Despite the promise of RNAi as a tool for functional genomics, injection of dsRNA interferes with gene expression transiently and is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
254
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(264 citation statements)
references
References 16 publications
3
254
0
5
Order By: Relevance
“…When we reduced LKB1 expression in the thorax region by a complementary RNA hairpin corresponding to LKB1 mRNA (LKBi), thoracic morphogenesis was significantly disrupted with bristle and scutellum formation defects ( Supplementary Figure 4a-d). 53 The same phenotypes were consistently observed with comparable penetrances (Supplementary Figure 4e) when dsRNAi was generated by other approaches such as usage of the hairpin construct with the inversed orientation (Inv) and of the SympUAST vector inducing symmetrical transcription to generate dsRNAi (Sym). 53,54 Therefore, we concluded that LKB1 is involved in the thoracic morphogenetic processes.…”
Section: Lkb1 Genetically Interacts With Jnk During Thoracic Morphogesupporting
confidence: 56%
See 3 more Smart Citations
“…When we reduced LKB1 expression in the thorax region by a complementary RNA hairpin corresponding to LKB1 mRNA (LKBi), thoracic morphogenesis was significantly disrupted with bristle and scutellum formation defects ( Supplementary Figure 4a-d). 53 The same phenotypes were consistently observed with comparable penetrances (Supplementary Figure 4e) when dsRNAi was generated by other approaches such as usage of the hairpin construct with the inversed orientation (Inv) and of the SympUAST vector inducing symmetrical transcription to generate dsRNAi (Sym). 53,54 Therefore, we concluded that LKB1 is involved in the thoracic morphogenetic processes.…”
Section: Lkb1 Genetically Interacts With Jnk During Thoracic Morphogesupporting
confidence: 56%
“…53 The same phenotypes were consistently observed with comparable penetrances (Supplementary Figure 4e) when dsRNAi was generated by other approaches such as usage of the hairpin construct with the inversed orientation (Inv) and of the SympUAST vector inducing symmetrical transcription to generate dsRNAi (Sym). 53,54 Therefore, we concluded that LKB1 is involved in the thoracic morphogenetic processes.…”
Section: Lkb1 Genetically Interacts With Jnk During Thoracic Morphogesupporting
confidence: 56%
See 2 more Smart Citations
“…However, several reports have recently demonstrated that the transcription of an inverted repeat from a transgene can form a hairpin loop in vivo. Furthermore, by utilizing the power of the Drosophila genetics and the GAL4/UAS binary system (Brand and Perrimon, 1993), one can express these hairpin RNAs in a temporal and spatialspecific manner in transgenic animals (Fortier and Belote, 2000;Kennerdell and Carthew, 2000).…”
mentioning
confidence: 99%